Necrotizing fasciitis that led to unexpected and fulminant deterioration in less than 24 hours: a case report - Deborah K. Becker; Meike Röder; Johannes Wagenhäuser; Sebastian Eichberger; Monika Herten; Marcel Dudda (Journal of International Medical Research)
Necrotizing fasciitis (NF) is a rapidly progressing condition with a high mortality rate. The poor prognosis is often due to delayed diagnosis, which is typically made clinically or radiologically. This case report highlights a rare instance of fulminant NF with an atypical presentation—no initial clinical signs and an unusual radiological appearance. Both the localization and microbiological findings (non-resistant Klebsiella pneumoniae ) were uncommon for NF. The patient presented with no suspicious skin changes, pain, or medical history indicative of NF. A computed tomography scan revealed entrapped air, a pathognomonic sign of NF; however, the air was predominantly located in the abdomen, leading to an initial suspicion of hollow organ perforation because this is an unusual location for NF. Subsequently, NF was suspected based on the computed tomography findings combined with laboratory results. Despite prompt surgical intervention and broad-spectrum antibiotic therapy, the patient died of multi-organ failure within 16 hours. This case underscores the importance of recognizing the subtle and varied presentations of NF and using tools such as the Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) score. Healthcare providers must maintain a high index of suspicion for NF, even when clinical, radiological, and laboratory findings seem inconspicuous.